2022
DOI: 10.1021/acs.jpclett.1c03893
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Self-Assembly of Phenyleneethynylenes under Vibrational Strong Coupling

Abstract: The chemical and physical properties of molecules and materials are known to be modified significantly under vibrational strong coupling (VSC). In order to gain insight into the effects of VSC on − interactions involved in molecular self-assembly, themselves sensitive to vacuum electromagnetic field fluctuations, the aggregation of two structural isomers (linear and V-shaped) of phenyleneethynylene under cooperative coupling was investigated. By coupling the aromatic C=C stretching band, the assembly of one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…Under these conditions, a system is said to enter the vibrational strong coupling (VSC) regime, ,, which leads to the formation of two vibro-polaritonic bands (P+ and P−) and dark states (DS) as shown in Figure A. This exotic interaction is mediated by EM fluctuations and therefore occurs even in the dark. , Over the past decade, it has been shown that VSC modifies a variety of chemical properties, such as reaction kinetics, chemo- and stereoselectivity, ionic conductivity, the rate of vibrational energy transfer, selective crystallization, or self-assembly. , The detailed mechanism at work is, however, still elusive, and more experimental results and theoretical analysis are needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, a system is said to enter the vibrational strong coupling (VSC) regime, ,, which leads to the formation of two vibro-polaritonic bands (P+ and P−) and dark states (DS) as shown in Figure A. This exotic interaction is mediated by EM fluctuations and therefore occurs even in the dark. , Over the past decade, it has been shown that VSC modifies a variety of chemical properties, such as reaction kinetics, chemo- and stereoselectivity, ionic conductivity, the rate of vibrational energy transfer, selective crystallization, or self-assembly. , The detailed mechanism at work is, however, still elusive, and more experimental results and theoretical analysis are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In a microscopic perspective of solvation (microsolvation), local interactions such as hydrogen bonding or dispersion interactions can also potentially be modified under strong coupling. Accordingly, solvation-sensitive systems, such as self-assembly, , enzyme-catalyzed reactions, , and proton transfers, , have been shown or predicted to be impacted by VSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulations in intermolecular interactions, ground state potential landscape, and other molecular parameters inside the resonant cavity are the driving force for polariton chemistry. 56−58 Other than reaction rate modification, direct manifestation of such cavity effects has recently been reported by several groups, including altered self-assembly structures of conjugated polymers 59,60 and modified ion conductivity under vibrational strong coupling. 61 It is beyond the scope of this paper to discuss quantitatively the origin of modified orientational factors inside the cavity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…reported that the cooperative VSC of the solvent could also decelerate a chemical reaction by coupling the solvent vibrational band [37] . Cooperative VSC has also been shown to be efficient in modifying super‐conductivity, ferromagnetism, supramolecular assembly, selective crystallization processes, etc [38–42] …”
Section: Introductionmentioning
confidence: 99%